2020
DOI: 10.1136/postgradmedj-2019-137484
|View full text |Cite
|
Sign up to set email alerts
|

Application of Failure Mode and Effect Analysis (FMEA) to improve medication safety: a systematic review

Abstract: Medication safety is a phenomenon of interest in most healthcare settings worldwide. Failure Mode and Effect Analysis (FMEA) is a prospective method to identify failures. We systematically reviewed the application of FMEA in improving medication safety in the medication use process. Electronic databases were searched using keywords ((failure mode and effect analysis) AND (pharmacy OR hospital)). Articles that fulfilled prespecified inclusion criteria were selected and were then screened independently by two re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
24
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 35 publications
(30 citation statements)
references
References 38 publications
0
24
0
Order By: Relevance
“…PubMed, JSTOR, Emerald, SAGE, Wiley online, Oxford journals, Web of science, Scopus and Cochrane library databases were searched for relevant studies from January 2006 to December 2017 (27). During this review, we found a number of studies using FMEA in areas such as chemotherapy (11)(12)(13)(14), parenteral nutrition (28), medication management (2,29,30), medication administration (31,32), medication use process (one or more steps from prescribing to dispensing) among in-patients (18,33,34) and paediatrics (12,(15)(16)(17)23).…”
Section: Discussionmentioning
confidence: 99%
“…PubMed, JSTOR, Emerald, SAGE, Wiley online, Oxford journals, Web of science, Scopus and Cochrane library databases were searched for relevant studies from January 2006 to December 2017 (27). During this review, we found a number of studies using FMEA in areas such as chemotherapy (11)(12)(13)(14), parenteral nutrition (28), medication management (2,29,30), medication administration (31,32), medication use process (one or more steps from prescribing to dispensing) among in-patients (18,33,34) and paediatrics (12,(15)(16)(17)23).…”
Section: Discussionmentioning
confidence: 99%
“…In a 2021 systematic review of 33 articles about medication safety, 31 had corrective actions recommended. 21 Anjalee et al 21 found that 6 articles reported a reduction in errors. In addition, the perceptions of FMEA participants about its advantages were reported; these included the ability to gather the collective knowledge of the team, analyze complex processes, increase clinicians' awareness of health care risks, and promote safety.…”
Section: Discussionmentioning
confidence: 99%
“…Several drawbacks were listed as well, such as being a time-consuming process, subjective in nature, and having a single-institution focus. 21 …”
Section: Discussionmentioning
confidence: 99%
“…Accordingly, it is of vital importance to reduce risk proactively. Failure Mode and Effect Analysis (FMEA), a valuable prospective analysis that incorporates methods for identifying failure modes, and their causes and effects ( 22 ), was first used in the aerospace industry in the mid-1960 s ( 23 ). It has since been revised and applied to healthcare by the Joint Commission on Accreditation of Healthcare Organizations in 2001, which has been renamed the Healthcare Failure Mode and Effect Analysis (HFMEA) ( 23 ).…”
Section: Introductionmentioning
confidence: 99%